From matter to artifact conveying the sacred: the ritual laurel of St. Sylvester in Troina - Ginex, Maurilio (E|C, 2023)
In the contexts of popular religiosity, material culture has a considerable weight in identity capital. Matter, in its most multifaceted forms and through a powerful process of agency, has the power to transform contexts according to the uses made of it and to generate forms of aggregation around it. It can also build an entire ceremonial structure that identifies a cultural context around it. This is the case of Troina, a town in the Enna district of Sicily. Troina’s festive calendar includes a feast in honour of its patron saint: San Silvestro. A pilgrimage that moves from the village towards a dimension, a sacred one, of the extra-urban, the forest, where only one thing counts: a tuccata ru ‘ddauru. The touch of the laurel, the plant that conveys the sense of the sacred, underpins a pilgrimage that has been taking place for centuries in a territory of devotees.